A review on TiO2/g-C3N4 visible-light- responsive photocatalysts for sustainable energy generation and environmental remediation. Issue 4 (August 2020) - Acharya, Rashmi; Parida, Kulamani
Abstract: Semiconductor based photocatalysis has been considered as a propitious technology to resolve sustainably energy scarcity and environmental pollution across the globe. Though TiO2 and graphitic carbon nitride (g-C3 N4 ) has extensively been investigated among various semiconductors, their prospective applications are restricted due to high rate of recombination of photoinduced charge carriers. Moreover, the UV active wide band gap of TiO2 limits it utilization of inexhaustible solar radiation, which consists of only 7 % of UV component. In this review, these issues have been addressed with illustration of different strategies employed for construction of TiO2 /g-C3 N4 (TGCN) heterojunction. We have overviewed various synthetic routes for TGCN heterojunction construction and principles for construction of Type II and Z scheme TGCN heterojunctions. Different morphology based TGCN heterostructures such as mesoporous, core-shell, point-to-face (0D/2D), line-to-face (1D/2D) and face to face (2D/2D) architectures were systematically discussed. The enhanced photocatalytic activity of morphology based TGCN heterojunctions with respect to H2 generation and environmental remediation in terms of NO oxidation, CO2 conversion, Cr (VI) reduction, dye degradation, organics removal and antibiotics decontamination are thoroughly reviewed. Photoelectrochemical water oxidation over TGCN electrode was succinctly described. Mechanism of pollutant degradation was highlighted by the demonstration of radical trapping experiments, electron spin resonance spectroscopy (ESR) and electron paramagnetic resonance spectroscopy (EPR). The stability of TGCN heterojunctions was also illustrated. Limitations and challenges of TGCN heterojunction photocatlytic system were briefly depicted in this review. The future perspectives for commercialisation of this photocatalytic system in production of H2 energy and degradation of pollutants were presented.